Science in the Press in Nine Latin American Countries - Massarani, Luisa; Buys, Bruno (Brazilian journalism research, 2007)
The objective of this article is to present a panorama of the journalistic coverage of science and technology themes in Latin America, taking as a case study 12 newspapers of signifcant impact in the region, involving nine countries. We collected the stories published in the science section from January to April 2006, and analyzed them based on the constructed week methodology and using quantitative tools. In total, our sample amounted to 681 stories. Among our fndings, we observed an important presence of medicine and health issues as main topics of the stories. National science has space in the newspapers, although less than scientifc results from developed countries. Benefts are stressed in the stories, while a low level of controversies is observed. Scientists are the main source for the journalists, with a low representation of the former in stereotyped images in most of the newspapers.